Dynamics of resistant hypertension in the postoperative period of carotid endarterectomy with and without carotid body saving - A. N. Kazantsev; R. A. Vinogradov; M. A. Chernyavsky; V. N. Kravchuk; D. V. Shmatov; A. A. Sorokin; A. A. Erofeev; V. A. Lutsenko; R. V. Sultanov; A. R. Shabaev; I. M. Radzhabov; G. Sh. Bagdavadze; et al. (Российский кардиологический журнал, 2021)
Aim. To analyze the results of multicenter study on dynamics of resistant hypertension (RH) in patients after various types of carotid endarterectomy (CE) with and without carotid body savingMaterial and methods. During the period from January 2010 to December 2020, 1827 patients with hemodynamically significant stenosis of the internal carotid artery (ICA) and RH were operated on. Depending on CE type, the two groups were selected. Group 1 (n=1135; 62,2%) consisted of patients received glomus-saving surgery: 19,2% (n=351) -conventional CE with a patch repair of reconstitution point; 13,6% (n=248) — glomus-saving CE sensu R. A. Vinogradov; 7,3% (n=133) — glomus-saving CE sensu K. A. Antsupov; 11,7% (n=214) — glomus-saving CE sensu A. N. Kazantsev; 4,6% (n=84) — Chick-Chirik CE; 5,7% (n=105) — swallow tail type patch repair sensu R. I. Izhbuldin. Group 2 (n=692; 37,8%) consisted of patients received CE without glomus saving: 18,6% (n=341) — eversion CE with carotid body cutoff; 6,3% (n=115) — CE with new bifurcation plasty; 5,85% (n=107) — autoarterial reconstruction; 7,1% (n=129) ICA autotransplantation sensu E. V. Rosseikin.Results. The mortality rate, as well as the prevalence of myocardial infarction (MI) and ischemic strokes were comparable in groups. The incidence of hemorrhagic transformation (group 1: 0%; group 2: 0,6%; p=0,04; OR=0,06; 95% CI, 0,003-1,25) and composite endpoint (death+MI+ischemic stroke+hemorrhagic transformation) (group 1: 1,06%; group 2: 3,0%; p=0,004; odds ratio (OR)=0,34; 95% CI, 0,16-0,69) significantly differs between groups. After glomus-saving CE, the number of patients with the target blood pressure (BP) level reached 51,1% (p <0,0001; OR=0,0009; 95% CI, 6,05-15,9). The number of patients with grade II (31,1%; p<0,0001; OR=12,7; 95% CI, 10,4-15,52) and III (3,6%; p<0,0001; OR=10,26; 95% CI, 6,71-15,67) hypertension significantly decreased. In the group 2, the prevalence grade III hypertension increased (48,0%; p<0,0001; OR=0,23; 95% CI, 0,18-0,3), while the number of patients with grade I (0%; p<0,0001; OR=77,0; 95% CI, 4,71-12,58) and II (52%; p<0,0001; OR=3,06; 95% CI, 2,43-3,86) hypertension decreased.Conclusion. Glomus-saving CE contributes to achieving target BP in patients with RH. Its removal increases the risks of labile hypertension, postoperative hypertensive crisis, hyperperfusion syndrome and hemorrhagic transformation.